The Serbian–Russian and Russian–Serbian Idiomatic Dictionary for Expressing Emotions: Theoretical and Practical Aspects - Mrkaić, Milena (Lexikos, 2025)
This article presents the development of the Serbian–Russian and Russian–Serbian Dictionary of Emotion-Expressing Idioms (SRIDE). The project aims to systematise idioms that convey emotional expression in Serbian and Russian, taking into account their cultural, linguistic, and cognitive aspects. The author designs a specialised dictionary based on data from the Serbian web corpus (srWaC) and the Russian National Corpus (RNC), compiled at the Department of Russian Language and Literature at the University of Montenegro. Material collection has been ongoing since 2020, with the phraseological database continuously expanding. The methodological foundation of the study is a comprehensive analysis of existing monolingual and bilingual dictionaries, which has identified key challenges, such as idiom polysemy and equivalence issues. The project employs a thematic classification of material based on twelve basic emotions defined by Izard's model. Each dictionary entry is meticulously structured, including a thematic heading, adaptive index, transcription, grammatical information, definition, usage examples, etymological notes, equivalents, and antonyms. The implementation of the OnLex electronic platform enhances functionality, offering multimedia storage and automated search capabilities. The findings demonstrate that integrating traditional lexicographic methods with modern technologies enables the creation of a reliable tool for cross-cultural analysis, language teaching, and translation, catering to the needs of linguists, translators, educators, and students.Keywords: equivalence, emotions, bilingual dictionaries, Serbian–Russian idioms, corpus analysis, comparative lexicography, multi-aspect classification